PENERIMAAN PANELIS DAN ANALISIS USAHA MI INSTAN DARI TEPUNG JAGUNG LOKAL RIAU DAN PATI SAGU - Morda, Oktopria; Pato, Usman; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimed to analyze the level of acceptance by the panelists and to analyze the business of instant noodles made from Riau local corn flour and sago starch. The research was conducted experimentally by making instant noodles from Riau local corn flour and sago starch. Parameters observed were acceptance of panelist and business analysis. Data of acceptance panelist were analyzed by Cochran's Q test at the level of 5%. The result of Cochran's Q test indicated the number of 3,529 and Asymptotic Significance 0,317 with the understanding that the instant noodles made from Riau local corn flour and sago starch were accepted by the panelists. Business analysis of instant noodles made from Riau local corn flour and sago starch show that profit obtained were Rp. 223.518,58; business efficiency with RCR were 1.54; BEP based on the amount of production value were 207,24 and the BEP based on production price were Rp. 1.299,31 and economic added value were Rp. 243.810,00. Keywords : Riau local corn flour, sago starch, instant noodles, panelist acceptance, business analysis.